(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
جُمعت وصُنفت أربعة أنواع من جنس القراص Urtica L، وهي: Urtica hulensis Feinbr , Urtica urens L ., Urtica membranacea Poir و Urtica pilulifera L . و لأول مرة سجل النوع U . hulensis في الفلورا السورية من خلال هذه الدراسة اعتماداً على كلٍ من ( Mouterde , 1983 ) , ( Post , 1933 ) . صُنفت الأنواع بالاعتماد على الصفات المورفولوجية للأوراق، وشكل وعدد الأذينات، النورات المؤنثة والنورات المذكر، الأزهار المؤنثة والأزهار المذكرة، والبذور . بينت دراسة حبات الطلع في الأنواع المدروسة أنها كروية الشكل وتحوي من (3-4 ) ثقوب انتاش، وبلغ متوسط قطر حبات الطلع 12,4 ميكروميتر . The following four species of genus Urtica L. were collected and classified: Urtica pilulifera L., Urtica membranacea poir., Urtica urerns L., Urtica hulensis Feinbr. The species Urtica hulensis was recorded for the first time in the Syrian flora in this study according to (Post, 1933); (Mouterde, 1983). Species were classified depending on morphological characteristics of number of leaves and form of stipules, female and male inflorescences, female and male flowers, and seeds. Pollen study of studied species was clarified as having globose shape and contain 3-4 pores, and the average diameter of pollen grain was 12.4µm.